An evaluation of problem-solving strategies taught in grade 9 english first additional language classrooms in selected schools in Capricorn District, Limpopo Province, South Africa - Ntatamala, Motlatjo (My University, 2019)
The aim of the study was to evaluate the extent to which problem-solving strategies are taught in the Grade 9 English First Additional Language classrooms in selected schools in Capricorn district, Limpopo, South Africa. The research was a case study in design. A qualitative approach was used. The data collection instruments included an observation checklist, interview questions for the teachers and the data was collected through both observing the teachers in the classroom and interviewing them as well as from the language activities done in learners‘ workbooks. Portfolios, files and journals of Grade 9 learners were thoroughly studied to ascertain whether problem-solving skills were applied, if at all. Three grade 9 English First Additional Language (EFAL) classes in three high schools were observed and six educators from the grade 9 EFAL classes were interviewed. The themes extracted from the data were for the purpose of determining whether EFAL educators from three secondary schools in Limpopo teach problem-solving as a learning strategy, to determine the extent to which the educators are aware of and recognise problem-solving strategies in the teaching of English in the Grade 9 classroom and to establish the kind of problem-solving activities, if any, educators use in their lessons. The relevant literature was reviewed to gain insight into problem-solving strategies in EFAL classrooms. The literature review was divided into Problem-Solving and Reading Comprehension as a Cognitive Process and Task-Based Language Teaching (TBLT) and Zone of Proximal Development (ZPD). Educators in this study experience challenges in teaching problem-solving strategies as well teaching learners to master problem-solving strategies. Learners encounter challenges in applying such strategies in their learning, reading and writing as evident in the tasks and activities set for them. The educators experienced these challenges because they did not know how to use those strategies. It appears the strategy was not part of their teacher training nor did they get the chance later in their careers to receive training in the new curriculum changes and learning strategies such as problemsolving. v From my observations, all the learners had problem-solving skills, but they just did not have the confidence to apply those skills because they lacked the confidence in class. Some had problems using English as the language of learning. However, there were learners who possessed problem-solving skills, who knew how and when to apply those skills. Those learners were confident enough to stand in front of the whole class and give a presentation on the given activities that were done in pairs and in groups. For instance, when I checked their workbooks, comprehension texts were covered, and pre-activities based on the novel that they were reading in class were also covered as well as the group activities. I made copies of the selected activities that they did on problem solving from their workbooks as well as their textbooks, which I have attached as appendices at the end of the report. However, group work and peer teaching which enhance mastery of problem-solving skills were the least used. The Department of Education should arrange a teacher‘s training workshop specifically on problem-solving, in order to improve the educators‘ problem-solving teaching strategies, since most educators, especially those who obtained their teaching qualification with a 3-year diploma, find it difficult to relinquish their old teaching methods and adapt to newer strategies such as problem-solving.
Thesis (M. A. (English Language Studies) -- University of Limpopo, 2019
Keywords: Problem-solving strategies; Teaching; Learning; Educational training; English language -- Study and teaching (Higher) -- South Africa -- Limpopo; English language -- Study and teaching -- Foreign speakers; Teaching; Second language acquisition